Comparison Between Blood-Brain Barrier Water Exchange Rate and Permeability to Gadolinium-Based Contrast Agent in an Elderly Cohort - Shao, Xingfeng; Jann, Kay; Ma, Samantha J.; Yan, Lirong; Montagne, Axel; Ringman, John M.; Zlokovic, Berislav V.; Wang, Danny J. J. (Frontiers in Neuroscience, 2020)
Background: Dynamic contrast‐enhanced (DCE) MRI using intravenous injection of gadolinium-based contrast agents (GBCAs) is commonly used for imaging blood-brain barrier (BBB) permeability. Water is an alternative endogenous tracer with limited exchange rate across the BBB. A direct comparison between BBB water exchange rate and BBB permeability to GBCA is missing. The purpose of this study was to directly compare BBB permeability to GBCA (Ktrans and kGad = Ktrans/Vp) and water exchange rate (kw) in a cohort of elderly subjects at risk of cerebral small vessel disease (cSVD). Methods: Ktrans/kGad and kw were measured by DCE-MRI and diffusion prepared pseudo-continuous arterial spin labeling (DP-pCASL), respectively, at 3 Tesla in 16 elderly subjects (3 male, age=67.9±3.0yrs) at risk of cSVD. The test‐retest reproducibility of kw measurements was evaluated with repeated scans ~6 weeks apart. Mixed effects linear regression was performed in the whole brain, gray matter (GM), white matter (WM), and 6 subcortical brain regions to investigate associations between Ktrans/kGad and test-retest kw. In addition, kw and Ktrans/kGad were compared in normal appearing white matter (NAWM), white matter hyperintensity (WMH) lesions and penumbra. Results: Significant correlation was found between kw and Ktrans only in WM (β=6.7×104, P=0.036), caudate (β=8.6×104, P=0.029) and middle cerebral artery (MCA) perforator territory (β=6.9×104, P=0.009), but not in the whole brain, GM or rest 5 brain regions. Significant correlation was found between kw and kGad in MCA perforator territory (β = 1.5×103, P = 0.049), medial-temporal lobe (β = 3.5×103, P = 0.032) and hippocampus (β = 3.4×103, P = 0.038), but not in the rest brain regions. Good reproducibility of kw measurements (ICC=0.75) was achieved. Ktrans was significantly lower inside WMH than WMH penumbra (16.2%, P=0.026), and kGad was significantly lower in NAWM than in the WMH penumbra (20.8%, P < 0.001). Conclusion: kw provides a measure of water exchange rate across the BBB with good test-retest reproducibility. The BBB mechanism underlying kw and Ktrans/kGad is likely to be different, as manifested by correlations in only three brain regions for each pair of comparison between kw and Ktrans or kGad.